PERAN STRATEGIS MANAJEMEN SUMBER DAYA MANUSIA KANTOR HUKUM LAURENSIUS ARLIMAN SIMBOLON DAN PARTNERS DALAM PENINGKATAN DAYA SAING DI KOTA PADANG - Tamba, Imelda (Ensiklopedia Sosial Review, 2019)
As one of the pillars of the company's functions, human resource management is a major milestone in considering the decision making of three other functions: finance, marketing, operations / production. Human resources in the company are the most valuable assets. Optimizing the results of the company's achievements will be strongly supported by the increasing role of functional managers involved in managing human resources. Human resource management is part of management science that focuses its attention on regulating the role of human resources in the activities of an organization. In achieving its goals, of course, an organization needs human resources as a manager of the system, so that the system runs certainly in its management, it must pay attention to several important aspects such as training, development, motivation and other aspects. This will make human resource management an important indicator of achieving organizational goals effectively and efficiently.